Interface interaction between silica and organic macromolecule conditioned forward osmosis membranes: Insights into quantitative thermodynamics and dynamics. (1st April 2023) - Zhu, Xianzheng; Tian, Tuo; Li, Danyang; Hei, Shengqiang; Chen, Lu; Song, Guangqing; Lin, Weichen; Huang, Xia
Highlights: Organic conditioning of FO membranes prominently enhanced silica scaling. Membrane surface charge induced macromolecules play a key role in silica scaling. Binding reaction between the silica and LYZ was more thermodynamically favorable. The interaction energy of silica–membrane and silica–macromolecules was measured. Electrostatic interaction was the dominant force between silica and membrane. Abstract: Silica scaling is a rising concern in forward osmosis membrane-based water treatment process. The coexistence of ubiquitous organic macromolecules causes complex silica scaling. The silica scaling mechanism on the surface of the organic conditioned membrane remains unclear. An integrated multi scale thermodynamic and dynamic approach was used in this study to provide in-depth insights into the binding effect at the interface between the silica and the organic conditioned membrane at the molecular level. Sodium alginate (SA) was used as the model polysaccharide, bovine serum albumin (BSA) and lysozyme (LYZ) were chosen as two oppositely charged proteins. The results show that the silica scaling degree of different organic conditioned membranes follows the order LYZ > BSA > SA. The binding strength between silica and organic macromolecules and the membrane surface charge are the major factors governing the degree of silica scaling. Quartz crystal microbalance with dissipation (QCM-D), isothermal titration calorimetry (ITC), and extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) model analyses were conducted to quantify the binding capacity of silica to the organic conditioned membrane. The LYZ conditioned membrane exhibits the highest affinity for silica adsorption, and electrostatic interaction was the main molecular interaction force. This study provides fresh insights into how silica and an organic conditioned membrane interact and induce silica scaling, providing new information on potential mechanisms and control strategies to prevent membrane scaling. Graphical abstract: Image, graphical abstract